2001
DOI: 10.1007/bf02864866
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on the role of yoga asanas on oxidative stress in non-insulin dependent diabetes mellitus

Abstract: Nineteen subjects of non-insulin dependent diabetes mellitus (NIDDM) between the age group of 30 -60 yrs were studied to see the effect of specific yoga asanas on fasting and postprandial blood glucose (FBG, PPG), serum malondialdehyde (MDA) and glycosylated hemoglobin (HbA~) in addition to drug treatment and diet control. The duration of diabetes ranged from I -10 years. Patients with renal, cardiac and proliferative retinal diseases were excluded from the study. The same patients served as their own control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 17 publications
3
51
1
Order By: Relevance
“…Documented changes included reductions in fasting 68,80,85,86,88 -90,92,93 and postprandial glucose, 85,86,89,91,92 and in fasting glycohemoglobin; [85][86][87] in the one uncontrolled study yielding negative results, a trend toward reduced glucose was observed in male subjects despite low baseline levels 94 (Table 4). Likewise, nonrandomized controlled studies of healthy young adults 88 and adults with coronary artery disease (CAD) 80 reported reductions in fasting glucose among subjects receiving a yoga-based intervention versus controls receiving enhanced usual care 80 or no active intervention 88 ; descriptive findings of an additional small controlled study of healthy young men suggested similar improvement following a prescribed yoga program.…”
Section: Markers Of Insulin Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…Documented changes included reductions in fasting 68,80,85,86,88 -90,92,93 and postprandial glucose, 85,86,89,91,92 and in fasting glycohemoglobin; [85][86][87] in the one uncontrolled study yielding negative results, a trend toward reduced glucose was observed in male subjects despite low baseline levels 94 (Table 4). Likewise, nonrandomized controlled studies of healthy young adults 88 and adults with coronary artery disease (CAD) 80 reported reductions in fasting glucose among subjects receiving a yoga-based intervention versus controls receiving enhanced usual care 80 or no active intervention 88 ; descriptive findings of an additional small controlled study of healthy young men suggested similar improvement following a prescribed yoga program.…”
Section: Markers Of Insulin Resistancementioning
confidence: 99%
“…Although the evidence for a beneficial effect of yoga on indices of insulin resistance is relatively consistent across studies, most studies (62%) had no comparison groups 68,85,86,89 -92,94 and many had small sample sizes 68,85,86,89,90,93,95 or reduced power due to stratified analyses. 87,92,94 Others lacked detailed information on eligibility criteria or study population characteristics, 80,85,86,88,89,93 and blinding of the outcome assessment was reported in only one study.…”
Section: Markers Of Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations